1983
DOI: 10.1159/000137799
|View full text |Cite
|
Sign up to set email alerts
|

Structure Activity Correlation for Diuretic Furosemide Congeners

Abstract: The structure activity correlation of several groups of anthranilic acid derivatives was studied. 59 compounds, most of them possessing the anthranilic acid moiety, were synthesized and tested for diuretic and saluretic activities. Equations correlating the biological activities of these compounds with their physicochemical constants suggest positive dependence of the diuretic activity on log P (octanol: water partition coefficient). It is concluded that, within limits, the variation in biological activity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Substitution of one or two methyl groups for one or two hydrogen atoms in the sulphamoyl nitrogen in the furosemide and bumetanide series of diuretics may either change the diuretic potency or induce a thiazide type of action (Tvaermose Nielsen & Feit 1978, Allen 1983), the latter effect perhaps by shifts in the site of action within the nephron. This is one reason why data obtained in whole animals (Shani et al 1983) on the relationship between the structure and activity of such substituted diuretics are difficult to interpret. However, from experiments on perfused isolated rabbit TALH, in which the diuretic was administered in the close vicinity of the chloride-absorbing cell, Schlatter et al (1983) found that when one hydrogen in the sulphamoyl group was replaced by an alkyl chain not longer than four carbon atoms, in the case of bumetanide there was little change in the diuretic potency.…”
Section: Sulphamoyl Substituted Analogues Of Bumetanidementioning
confidence: 99%
“…Substitution of one or two methyl groups for one or two hydrogen atoms in the sulphamoyl nitrogen in the furosemide and bumetanide series of diuretics may either change the diuretic potency or induce a thiazide type of action (Tvaermose Nielsen & Feit 1978, Allen 1983), the latter effect perhaps by shifts in the site of action within the nephron. This is one reason why data obtained in whole animals (Shani et al 1983) on the relationship between the structure and activity of such substituted diuretics are difficult to interpret. However, from experiments on perfused isolated rabbit TALH, in which the diuretic was administered in the close vicinity of the chloride-absorbing cell, Schlatter et al (1983) found that when one hydrogen in the sulphamoyl group was replaced by an alkyl chain not longer than four carbon atoms, in the case of bumetanide there was little change in the diuretic potency.…”
Section: Sulphamoyl Substituted Analogues Of Bumetanidementioning
confidence: 99%